Improving Students’ Vocabulary Mastery through the Song “Let It Go” in the Seventh Grade of SMP PAB 2 Helvetia - Cindy Elsa Mayuri; Yenita Uswar (Universitas Muhammadiyah Enrekang, 2025)
This study was conducted to find out how the use of the song